Gardening activites during May-June - Sharma, Brij Bihari; Singh, Shrawan; Tomar, B S (Indian Horticulture, 2019)
Perform soil solarization for nursery beds by covering with plastic sheets to destruct eggs, larvae, pupa, spores etc. of soil borne pest/pathogen.